Implementasi Penjabaran Manajemen Sekuriti Berbasis Pancasila: Peran Closed Circuit Television (CCTV) Dalam Meningkatkan Keamanan di Kampus Universitas Bhayangkara Jakarta Raya - Nazlina, Kireina Zahra; Soesanto, Edy; Fauziah, Shyfa (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
The main aim of this research is to conduct an in-depth investigation into the role of closed circuit television (CCTV) in improving campus security at Bhayangkara University, Jakarta Raya. The aim of the research is to examine the implementation of the description of Pancasila-based security management, with a focus on the use of Closed Circuit Television (CCTV) in efforts to improve environmental security on the Bhayangkara University campus, Greater Jakarta. The results of the research hope that the installation of CCTV on the Bhayangkara Jakarta Raya campus will be effective in improving security, both as a detection tool and as a deterrent to crime. This study is motivated by the application of Pancasila values as an ideological basis for the Indonesian nation within the Bhayangkara University campus, Greater Jakarta, as Pancasila values which underlie all aspects of life and drive student character development within the campus environment to prevent criminal acts. Thus, the presence of CCTV also provides a better perception of security and comfort for academic members in the campus environment. The implication of this research is the importance of implementing CCTV technology in improving security in the campus environment to create a conducive learning environment which is based on Pancasila as the basic ideology of the Indonesian nation.